Changes in students’ life at selected uni- versities in Central and Eastern Europe during the first stage of the pandemic - KawczyńsKa-Butrym, Zofia; Pantyley, Victoriya; Butrym, Marek; Kisla, Ganna; Fakeyeva, Liudmila (Quaestiones Geographicae, 2022)
The COVID-19 pandemic affected not only global economy and society, but also particular institutions, in- cluding those of higher education. The aim of the paper is to determine changes in students’ life at selected universities in Poland, Ukraine, and Belarus. An online survey was applied, addressed to students of four universities in Poland, Ukraine, and Belarus (n=380). As a result of the pandemic, more than 46% of students declared worsening of their material situation. In comparison to the period before the pandemic, the respondents observed appearance or inten- sification of various psychosomatic symptoms, and a 12 percent point decrease in the assessment of their own health. The comparative analysis showed similarities between students’ life preferences, plans on university education, and differences in their material situation, health, and employment.